Risk of myocardial infarction in middle aged and older patients with coarctation of the aorta. (25th November 2020) - Fedchenko, M; Mandalenakis, Z; Giang, K.W; Eriksson, P; Rosengren, A; Dellborg, M
Abstract: Introduction: Previous case-control studies have compared the risk of coronary artery disease/myocardial infarction (MI) in patients with coarctation of the aorta (CoA) with other congenital heart disease diagnoses, however, these studies have only included younger patients in their 20s and 30s, not older patients. As the atherosclerotic burden is increasing with increasing age, it is important to study the risk of MI in older patients (from early middle age and older) with CoA. Purpose: The aim of our study was to investigate the risk of MI in older patients (≥40 years) with CoA, and to compare this risk with the risk in patients of the same age with ventricular septal defects (VSD), the most common congenital heart condition. Methods: We used data from the Swedish National Patient Registry (NPR) to identify all patients alive at 40 years of age with a diagnosis of CoA or VSD, born during the period 1930–1970. The follow-up through the NPR and the Cause-specific Death Registry started in January 1970 and went on until December 2017. Results: Altogether 1204 patients with CoA and 2079 patients with VSD were identified in the registers, and in total, 97 (8.1%) patients with CoA and 162 (7.8%) patients with VSD developed an MI during follow up. Mean follow up time was 20.6±10.3 years in CoA patients and 21.3±10.9 in the VSD group. The risk of MI was similar in CoA compared with VSD patients (HR 1.1, 95% confidence interval 0.9–1.5, p=0.3) Median age at MI was similar in CoA patients and in VSD patients; in CoA 59.8 years (range 40.1–87.5), in VSD 61.2 (range 40.2–87.5), p=0.3. Hypertension (diagnosed before MI or within a year after MI) was more common in CoA patients with an MI (58.8%) compared with VSD patients (37.7%), however, prevalence of diabetes mellitus and hyperlipidemia was similar in both patient groups (18.6% and 21.6% in CoA respectively, compared to 17.9% and 22.8% in VSD group). After adjustment for hypertension, diabetes mellitus and hyperlipidemia, the risk of MI remained similar in patients with CoA and VSD (hazard ratio 1.1, 95% confidence interval 0.8–1.4, p=0.5). Conclusion: In this large nationwide study, we found that in older patients with CoA (median age at MI 60 years, range 40–88 years) the risk of MI was not increased and similar to that of patients with VSD with similar age at MI. Adjustment for hypertension, diabetes mellitus and hyperlipidemia did not modify this finding which suggests that patients with CoA do not have an increased risk of MI, compared to patients with VSD. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This work was funded by the Swedish state under an agreement between the Swedish government and county councils, the ALF agreement (Grant number: 236611) and the Swedish Heart-Lung Foundation (Grant Number: 20090724).